2019
DOI: 10.1111/1462-2920.14593
|View full text |Cite
|
Sign up to set email alerts
|

Lignin catabolic pathways reveal unique characteristics of dye‐decolorizing peroxidases in Pseudomonas putida

Abstract: Summary Lignin is one of the largest carbon reservoirs in the environment, playing an important role in the global carbon cycle. However, lignin degradation in bacteria, especially non‐model organisms, has not been well characterized either enzymatically or genetically. Here, a lignin‐degrading bacterial strain, Pseudomonas putida A514, was used as the research model. Genomic and proteomic analyses suggested that two B subfamily dye‐decolorizing peroxidases (DypBs) were prominent in lignin depolymerization, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 54 publications
2
53
0
2
Order By: Relevance
“…Through this approach, we genetically investigated ferulic acid-to-PHA bioconversion in detail and further constructed the engineered P. putida KTc9n20 strain to successfully expand ferulic acid valorization, in addition to its well-known ferulic acid-to-vanillin biotransformation. Together with a microbial lignin depolymerization system under development 5 , exploration of PHA regulation mechanism under aromatic compounds, and further improvements in culture conditions in the near future, could provide insights into microbial carbon sink as well as improving lignin-consolidated bioprocessing schemes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through this approach, we genetically investigated ferulic acid-to-PHA bioconversion in detail and further constructed the engineered P. putida KTc9n20 strain to successfully expand ferulic acid valorization, in addition to its well-known ferulic acid-to-vanillin biotransformation. Together with a microbial lignin depolymerization system under development 5 , exploration of PHA regulation mechanism under aromatic compounds, and further improvements in culture conditions in the near future, could provide insights into microbial carbon sink as well as improving lignin-consolidated bioprocessing schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were lysed in the SDS loading buffer, and then supernatant cell lysates were subjected to 12% gel SDS-PAGE separation. In addition, Cas9n protein was purified by Ni-NTA column (Takara) and separated by SDS-PAGE as previously described 5 .…”
Section: Sds-page Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates tested include a variety of aromatic compounds classified as dyes [50,[53][54][55][56], beta-carotene [57], and aromatic sulfides [48]; some of which are poorly metabolized by other heme peroxidases. Numerous studies have shown that DyPs play a key role in the degradation of lignin [54,55,[58][59][60][61][62][63][64][65]. Their catalytic properties make them very interesting because the bacterial enzymes can be easily engineered, heterologously expressed in E. coli and purified [65] avoiding the issues of using a eukaryotic hosts.…”
Section: Dye-decolorizing Peroxidasesmentioning
confidence: 99%
“…The plasmid encodes a DyP-decolorizing peroxidase unit involved in detoxification. DyP decolorizing peroxidases of fungi and bacteria have an unknown physiological function, but wide biotechnological applicability as they degrade lignin and oxidize a variety of aromatic compounds, dyes, and other small molecules (Lin et al, 2019;Singh et al, 2013). A 32% identical DyP homolog is encoded on the Fec10 and E. coli K-12 chromosome.…”
Section: Pfec10 Is An Unconventional Plasmidmentioning
confidence: 99%